2019
DOI: 10.1111/codi.14595
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating predictive factors for determining the presence of lateral pelvic node metastasis in rectal cancer patients following neoadjuvant chemoradiotherapy

Abstract: Aim The need or otherwise for lateral pelvic node dissection (LPND) in rectal cancer patients with clinical lateral pelvic node metastasis (LPNM) after neoadjuvant chemoradiotherapy (nCRT) is controversial. This study was designed to explore the predictive factors for pathological LPNM in rectal cancer patients with clinical LPNM after nCRT.Method From January 2010 to February 2018, a consecutive series of patients with rectal cancer and clinical LPNM after nCRT who underwent total mesorectal excision and LPND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
(41 reference statements)
0
20
0
Order By: Relevance
“…In previous studies, the incidence of LPNM for patients with stage II-III rectal cancer was demonstrated to be 10–20% [ 1 , 2 ]. All the patients included in the present study were suspected of having LPNM by preoperative MRI evaluation, and the rate of pathological LPNM was only 20.5%, which is related to the relatively loose imaging diagnostic criteria of LPNM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, the incidence of LPNM for patients with stage II-III rectal cancer was demonstrated to be 10–20% [ 1 , 2 ]. All the patients included in the present study were suspected of having LPNM by preoperative MRI evaluation, and the rate of pathological LPNM was only 20.5%, which is related to the relatively loose imaging diagnostic criteria of LPNM.…”
Section: Discussionmentioning
confidence: 99%
“…The lateral pelvic lymph node (LPN) is one of the common lymphatic metastasis areas of middle-low rectal cancer, and it has been reported that approximately 10–20% of rectal cancer patients with stage II-III disease develop LPN metastasis (LPNM) outside the field of total mesorectal excision (TME) [ 1 , 2 ]. Most hospitals in Japan adopt a more active treatment attitude, and a prospective multicentre RCT (JCOG0212) conducted in Japan demonstrated that TME with ‘prophylactic’ LPN dissection (LPND) significantly decreased local recurrence rates compared with TME alone for patients who do not have LPN enlargement before surgery (7.4% vs 12.6%) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although open surgery was sometimes needed, most patients were placed in the modified lithotomy position for laparoscopic procedures regularly. The details of the LPND procedure have been described previously 12 . Briefly, unilateral or bilateral LPND was performed after removal of the rectum.…”
Section: Methodsmentioning
confidence: 99%
“…Informed consent has been obtained and procedures followed were Clinical LPNM was diagnosed by two imaging specialists who specialized in colorectal cancer based on MRI before treatment. The assessment criteria were described in our previous study 12 : (1) ≥0.8 cm in short diameter; (2) inhomogeneous or intense enhancement; and (3) irregular shape and rough edges. LPNM was diagnosed when one or more of the above criteria were met.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation